Amperometric Detection of dsDNA Using an Acridine‐Orange‐Modified Glucose Oxidase. Issue 11 (9th August 2017) - Jambrec, Daliborka; Lammers, Klaus; Bobrowski, Tim; Pöller, Sascha; Schuhmann, Wolfgang; Ruff, Adrian
Abstract: In the present "genomic era" and in the developing world of DNA chips, DNA detection based on intercalation of specific molecules is of particular interest because the detection process is largely independent of the sequence of the target DNA. In this work, an acridine‐orange‐based intercalation compound, which was tethered to deglycosylated glucose oxidase was synthesized ad hoc and investigated for its ability to interact with dsDNA. Amperometric detection of DNA hybridization was achieved by signal amplification based on the catalytic oxidation of glucose by DNA‐bound glucose oxidase. A clear distinction between dsDNA and ssDNA was achieved by careful design of a DNA‐modified electrode surface and prevention of nonspecific adsorption of the acridine‐orange‐modified enzyme by implementing a potential‐assisted immobilization method. Abstract : Orange sandwich : An acridine‐orange‐based intercalator bearing a 14‐atom‐long flexible spacer was tethered to deglycosylated glucose oxidase. The modified enzyme is useful for post‐labeling of double‐stranded DNA in one step by an intercalation process as a basis for amplified detection of DNA hybridization.